2014
DOI: 10.4236/sm.2014.43024
|View full text |Cite
|
Sign up to set email alerts
|

Race and Gender Differences in Obesity and Disease

Abstract: The objective of the present study was to examine race and gender differences in obesity and disease overtime. This topic is under studies in racial/ethnic minority populations. Yet, gender differences in health within ethnic groups provide a more nuanced approach to health disparities. The analyses for this study were based on two waves of data (Wave1, 1986 and Wave 2, 1989) of the Americans' Changing Lives Survey. The results revealed that a larger percentage of females are obese compared to males across all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
2
7
0
1
Order By: Relevance
“…Some studies suggest that the prevalence of obesity and sociodeterminants of obesity differ by gender [33][34][35][36]. For example, Jones-Johnson et al suggested that the prevalence of obesity was higher among women than men in all racial groups [35].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that the prevalence of obesity and sociodeterminants of obesity differ by gender [33][34][35][36]. For example, Jones-Johnson et al suggested that the prevalence of obesity was higher among women than men in all racial groups [35].…”
Section: Introductionmentioning
confidence: 99%
“…All other things being equal, such as age and exercise levels require fewer calories per kilogram of body weight daily than men and thus conserve more body fat. [29] Also, pregnancy and female hormones make it easier for women to gain weight. Again, women more often do the cooking in the households and so are likely to do a lot of eating while cooking.…”
Section: Discussionmentioning
confidence: 99%
“…First, we performed two ordered logistic regression models of participants’ BMI for the total sample, with and without food consumption behaviors. Next, gender-stratified models were conducted due to the gender gaps in obesity (Jones-Johnson, Johnson, & Frishman, 2014; Kanter & Caballero, 2012). The first two gender-stratified models, without food consumption behaviors, investigated the associations between older adults’ smoking frequency and BMI among male and female study participants.…”
Section: Methodsmentioning
confidence: 99%